2019
DOI: 10.1038/s41388-019-1074-1
|View full text |Cite
|
Sign up to set email alerts
|

Rho-mediated signaling promotes BRAF inhibitor resistance in de-differentiated melanoma cells

Abstract: Over half of cutaneous melanoma tumors have BRAF V600E/K mutations. Acquired resistance to BRAF inhibitors (BRAFi) remains a major hurdle in attaining durable therapeutic responses. In this study we demonstrate that approximately 50-60% of melanoma cell lines with vemurafenib resistance acquired in vitro show activation of RhoA family GTPases. In BRAFi-resistant melanoma cell lines and tumors, activation of RhoA is correlated with decreased expression of melanocyte lineage genes. Using a machine learning appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(112 citation statements)
references
References 78 publications
9
103
0
Order By: Relevance
“…Furthermore, by proteomic analysis, we demonstrated that DDR2 depletion with siRNA, DDR2 selective inhibition or Dasatinib treatment induce a decrease of RhoA signaling. Thoese results confirmed the recent study of Misek et al, which showed that in resistant cells there is an accumulation of actin stress fiber due to RhoA activation (Misek et al 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, by proteomic analysis, we demonstrated that DDR2 depletion with siRNA, DDR2 selective inhibition or Dasatinib treatment induce a decrease of RhoA signaling. Thoese results confirmed the recent study of Misek et al, which showed that in resistant cells there is an accumulation of actin stress fiber due to RhoA activation (Misek et al 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Cell lines, reagents, and antibodies: Parental (denoted by a P suffix in the cell line name) and matched isogenic BRAFiresistant cells (denoted by an R suffix in the cell line name) were either a gift (M229P/R, M238P/R) from Dr. Roger Lo (UCLA) or generated in our laboratory (UACC62P/R). These cells were generated and cultured as described below (47).…”
Section: Methodsmentioning
confidence: 99%
“…M229P/R and M238P/R RNA-Seq data was downloaded from GSE75313 (16). UACC62P/R RNA-Seq data was previously generated by our group and was deposited under GSE115938 (47). The PRISM drug response dataset was downloaded from the DepMap data download portal (depmap.org/portal/download).…”
Section: Flow Cytometrymentioning
confidence: 99%
See 2 more Smart Citations